Anyare sa bill? a Foucauldian analysis of the SOGIE Equality Bill in the Philippine Legislature - Roy, Wynezza Joyz P.; Yabut, Jerome Jeferson A.; Liwag-Lomibao, Ma. Aurora Lolita (Quezon City University of the Philippines, Diliman, 2025)
The SOGIE Equality Bill (SEB) is the longest-running legislative proposal in the Philippines. It was first introduced in 2000 and has been repeatedly refiled across more than two decades of Congress. While its legal and sociopolitical significance has been widely discussed, much less attention has been given to how its journey through the legislative system has been shaped by discourse and power relations. This study addresses that gap by critically analyzing the evolution of the bill through the lens of Michel Foucault’s (1972) Archaeological Method and complemented by Bourke and Lidstone’s (2015) methodological adaptation for policy analysis. By comparing and contrasting the 83 SOGIE-related anti-discrimination bills from the 11th-19th Congress, the study maps the discursive formations and institutional forces that have continuously shaped—and constrained—the bill’s development. Findings show that while the bill’s language becomes more inclusive and comprehensive, the bill’s progress is continually shaped and often stalled by political climates, strategic alliances, and institutional gatekeeping. Understanding these factors reveals the challenges of translating gender rights into legal protections. The trajectory of the SEB may serve as a reflective indicator of the Philippines’ progress toward gender equality, underscoring the need for sustained advocacy and deliberate policymaking to facilitate meaningful legislative reform.
Thesis
Keywords: Law and legislation -- 1926–1984 -- Political and social views; Sexual minorities -- Legal status, laws, etc. -- Philippines; Gender identity -- Law and legislation -- Philippines